Analysis of the Husband’s Support in the Readiness of Fertile-Age Women Regarding Pregnancy Preparation in Geger District Madiun Regency - Visi Prima Twin Putranti; Suharti Suharti (Alliance of Health Activists (AloHA), 2019)
Married couples generally want to get healthy childreen. The process of labor, pregnancy, and childbirth can be passed through the mother without complications if there is preparation long before the mother was declared pregnant. Physical and mental readiness should be sought by the mother to deal with the changes that will be experienced in pregnancy and the subsequent process. Support from the husband is thought to be an optimal factor in the success of the maternal and infant health. The purpose of this study is to determine the relationship of the husband’s support with the readiness of women in childbearing age in the preparation of pregnancy in Geger, Madiun. The research method used in this study is the cross sectional method. In Geger, Madiun the number of people which were married on July at were 60 couples. The sampling technique used was purposive sampling and the samples received were 36 respondents. The research variables involve independent variables of the husband’s support and dependent variables include the readiness of women of childbearing age in the preparation of pregnancy. The test validity used was the Pearson Product Moment. The reliability test used was the Alfa Cronbach. The collected data were analyzed by Chi-Square. The results showed that there was a significant relationship between husband’s support and the readiness of fertile-age women in pregnancy preparation, where number p was 0,018 (alpha = 0,05). The role of health workers to provide health education and motivation is expected to reduce morbidity and mortality of mothers and infants. Keywords: husband’s support; preparation of preganancy